Trans men's sexual narrative-practices: Introducing STS to trans and sexuality studies - Latham, Joe (Sage Publications, 2016)
Clinical expectations that trans people will be so filled with self-loathing that sexual interactions will be limited if possible at all fail to take into account the heterogeneous ways trans people experience their own bodies and sexualities. In this essay, I extend recent work in science and technology studies (STS) that attends to material practices by examining the work of narrative and argue for a new paradigm in situating trans sexualities. I analyse trans men's autobiographical stories to show some of the many ways that trans men make sense of themselves (and enact maleness) as sexual subjects. By focusing on how sex-gender is enacted and hangs together in narrative-practices, we can more fully understand and appreciate the realities of trans lives and the inadequacies of clinical diagnosis.